ダイ16ジ エットウ タイイン ノ タイナイ ホウシャセイ ブッシツ (137Cs, 40K) ノ ソクテイ ホウコク - 宮下, 充正; ミヤシタ, ミツマサ; 跡見, 順子; アトミ, ヨリコ; 上田, 慶子; ウエダ, ケイコ; Miyashita, Mitsumasa; Atomi, Yoriko; Ueda, Keiko (国立極地研究所, 1977)
P(論文) 本研究では,第16次越冬隊員21名に対し,ヒューマンカウンターを用いて,出発前および帰国直後,人体内に存在する放射性物質^<40>Kおよび^<137>Csを測定した.その目的は,(1)自然放射性物質に属する^<40>Kから全身カリウム量を求め,南極での生活が身体組成に及ぼす影響を推定すること,および(2)核爆発による放射性降下物である^<137>Csから,日本と南極における放射性物質の汚染の状態を人体を介して推察することである.結果は次の通りである.1)^<137>Csの測定値は,やまと山脈調査隊員6名では,出発前の1.20 nCiから1.69 nCi (p<0.05)へ有意に増加したが,基地隊員15名では,有意な変化はみられなかった.2)第16次越冬により,体重は有意に増加し(pく0.01),それに伴い全身カリウム量も有意に増加したが,皮下脂肪に変化はみられなかった. In this study, body burdens of cesium-137 and potassium-40 were measured using a human counter with 21 members of the 16th wintering party. The purposes of these measurements were (1) to observe the radioactive pollution in Japan and Antarctica through the human body, and (2) to estimate the effect of the Antarctic living on the body composition. The results obtained in the present study were as follows; 1) The mean value of body burdens of ^<137>Cs increased from 1.20 to 1.69 nCi (p<0.05) in the case of six traverse members of the Yamato Mountains, while there was no significant difference in the case of fifteen base members. 2) The mean value of body weights increased significantly (p<0.01) after the Antarctic living and accordingly the total body potassium increased significantly (p<0.05), while the body fat remained unchanged. departmental bulletin paper